Spirulina platensis DIET FOR MILKFISH, Chanos chanos, LARVAE - Purnama Sukardi; Noprie Yansah; Tjahyo Winanto; Sri Marnani; Norman Arie Prayogo; Taufan Harisam; Agung Sudaryono (SEAMEO BIOTROP, 2019)
In aquaculture, Spirulina platensis is used as a feed supplement as it contains the amino acid phenylalanine. This study was conducted to evaluate the differences in the effects of spirulina-based microcapsules and commercial diets on the absolute, daily, and specific growth rates, as well as the survival rates, of milkfish larvae. The larvae were fed with Spirulina platensis as a core diet in microcapsules with different matrix (wall) compositions. The first capsule wall consisted of gelatin and fish oil, while the second capsule wall contained gelatin, fish oil, and whole egg. The control group was fed a commercial diet. A total of 1,200 larvae were used in this experiment using a recirculating system. The experiment was conducted over 42 days of culture. The larvae were fed three times per day, and the feed amount was increased regularly in accordance with larval growth. The results showed that the effects of both spirulina-based microcapsule diets on absolute growth rate (AGR), specific growth rate (SGR), and average daily growth rate (ADGR) of Chanos chanos larvae were comparable to those fed a commercial diet. The survival rates were 80.6 ± 11.17% for larvae fed Spirulina platensis with a gelatin and fish oil wall, 84.6 ± 8.44% for those fed Spirulina platensis with a gelatin, fish oil, and whole egg wall, and 83.8 ± 16.50% for those fed the commercial diet. This study demonstrated that spirulina-based microcapsules had similar effects to commercial feed on the growth of milkfish larvae, indicating that this diet could potentially replace commercial feed.